To Evacuate or to Stay: Understanding the Behavioral Dynamics of Evacuation Decision-Making Among Communities Affected by the Semeru Eruption - Gde Abhicanika Pranata Dyaksa; I Dewa Made Frendika Septanaya; Adjie Pamungkas (Jurnal Penataan Ruang, 2025)
The delays and refusals to evacuate during the 2021 and 2022 Semeru eruptions indicate that multiple factors influenced the behavior of affected communities. This study investigates the drivers and constraint factors that shape evacuation decisions. Through a literature review, seven driving factors and seven constraining factors were identified. Data were collected via structured interviews with 100 residents from Supiturang and Sumberwuluh villages in the Lumajang district. Descriptive statistical analysis was employed to assess the influence of each factor on evacuation behavior. The findings reveal that all seven driving factors significantly influenced the decision to evacuate immediately, with the most prominent being the perceived threat of eruption hazards, such as seismic vibrations and volcanic ash. Conversely, only three of the seven constraining factors, concern for family safety, the evacuation behavior of neighbors, and the desire to protect personal assets, were found to contribute to delays or refusals to evacuate. These social and emotional considerations were central to postponing or disregarding evacuation orders. This research highlights critical gaps in current emergency response management, particularly in addressing the social dimensions of evacuation behavior. The results also highlight the need for targeted training and simulation exercises to enhance public understanding of eruption risks and evacuation protocols. Furthermore, the provision of appropriate facilities by authorities is essential to foster community compliance. Overall, this study contributes to a deeper understanding of the complex dynamics underlying evacuation decision-making in volcanic disaster contexts.